The relationship between health literacy, health status and health outcomes among German 4th-graders. (20th October 2021) - Bollweg, T; Okan, O; Freţian, A; Janner, C; Schulenkorf, T; Kirchhoff, S; Pinheiro, P; Bauer, U
Abstract: Background: The WHO describes Health literacy (HL) as a critical determinant of health, and a number of studies among adults link low HL to adverse health outcomes. However, little research has been conducted on HL and health outcomes in younger populations. Thus, this study describes the relationship between HL, health behaviors, and health status among children in primary schools. Methods: A cross-sectional pen-and-paper survey was conducted in a convenience sample of 4th-graders in the federal state of North Rhine-Westphalia, Germany. Self-report measures were used for subjective HL, health behaviors (freq. of brushing teeth, eating fruit, exercising, screen time), and health status (subj. health, chronic condition, freq. of doctor visits, feeling ill). Correlations and binary logistic regression for the outcome "at least one adverse health behavior" (e.g. brushing teeth <2x a day; not eating fruit every day) are reported. Sex, age, family affluence, background of migration, numeracy, literacy, and health knowledge are included in the regression model. Results: In our sample of n = 899 children (mean age 9, 56 years), HL is significantly correlated with subj. health (ρ=.262**) doctor visits (ρ=.086*), feeling ill (ρ=-.078*), brushing teeth (ρ=.116**), eating fruit (ρ=.191**) exercising (ρ=.124**) and screen time (ρ=-.096**). Logistic regression (X 2 =29.237; p=.001, n = 648) shows that the relative risk for ≥1 adverse health behaviour is higher for boys (OR: 1.4; 95%-CI [1.016-1.927]) and children with lowest family affluence (1.7 [1.097-2.694]). Also, for one unit increase in HL (range 1-4), risk decreases by about 50% (0.472 [.298-.748]). Conclusions: Already at a young age (9-10 years), HL is linked to a number of health outcomes. Further, HL has been found to be a potential predictor of adverse health behaviors after controlling for confounders.Thus, the promotion of HL might play an important role in mitigating adverse health behaviors early in the life course.